Embryo mortality and its relation with the phase of follicular development at mating in alpaca - Huanca López, Wilfredo; Cervantes, Miriam; Huanca Mamani, Teodosio (Wageningen Academic Publishers, 2023)
The objective of this study was to evaluate the relation between the phase of follicular development (growth, maintenance or regression) during mating with embryo mortality to day 35-post mating. 116 alpacas ≥ 3 years of age were examined daily by transrectal ultrasonography (Aloka SSD 500) using a 7.5 MHz linear-array transducer to evaluate follicular status and then assigned to the following groups G1: Growing follicle 5 - 6 mm (n = 27); G2: Growing ≥ 7 mm.(n=30); G3 Maintenance ≥ 7 mm. (n = 30); G4 Regressing follicle ≥7 mm. (n= 29). Ultrasounds examinations were performed on days 0, 2, 9, 20, 25, 30 and 35 to determine occurance of ovulation (day 2); Corpus Luteum diameter (CL (day 9) and presence of embryonic vesicle or embryo (day 20 to 35). Male acceptance, ovulation and conception rate was compared by Chi Square test between groups. Acceptance rate was 100% in groups G2,G3 and G4 but only 81.5% of animals of G1 with follicle of 6 mm. accepted mating. Ovulation rate was 95.5; 96.7; 100.0 and 96.6% in G1; G2; G3 and G4, respectively (P > 0.05) and no differences were detected between groups in CL diameter. Conception rate on day 20 was 57.1; 68.9; 60.0 and 50.0% for G1; G2; G3 and G4 (P > 0.05). Embryonic loss rates from day 20 to 35 were not significantly different between groups. This result suggest that the status of follicular development at mating would not have influence on embryo mortality rate between day 20 and 35 of gestation in alpacas and that animals that accepted mating in all phase, including the one with follicle of 6 mm diameter present similar reproductive performance.